Pain with Life-Threatening Illness: Its Perception and Control Are Inextricably Linked with Quality of Life. (1st December 2000) - Cohen, S Robin; Mount, Balfour M
Abstract : This article describes how the quality of life of people with a life-threatening illness is affected by pain, and how their pain is influenced by all aspects of their quality of life. These aspects include the physical, psychological, cognitive, social, and spiritual and existential domains. This concept of pain is placed in the context of Ron Melzack's work highlighting the essential role of cognitive and emotional aspects of pain perception, and their influence on pain control. These issues continue to be a guiding force in the authors' own work and that of many others working in the field.